การพัฒนาความสามารถในการแข่งขันของวิสาหกิจขนาดกลาง และขนาดย่อมโดยใช้แนวทางคลัสเตอร์: กรณีศึกษา คลัสเตอร์อุตสาหกรรมแปรรูปอาหารเพื่อสุขภาพ จังหวัดนครราชสีมา - โพธิ์ชาธาร สุธานันธ์ (Ratchaphruek Journal, 2016)
งานวิจัยนี้มีวัตถุประสงค์ เพื่อศึกษาขีดความสามารถในการแข่งขันของของผู้ประกอบการจากการรวมกลุ่มคลัสเตอร์อุตสาหกรรมอาหารแปรรูปเพื่อสุขภาพ จังหวัดนครราชสีมา จากการพัฒนาผู้ประกอบการ SMEs โดยใช้แนวทางการพัฒนาคลัสเตอร์ซึ่งเป็นรูปแบบของการวิจัยและพัฒนา ผลการวิจัย พบว่า ผู้ประกอบการที่เป็นสมาชิกในกลุ่มคลัสเตอร์อุตสาหกรรมอาหารแปรรูปเพื่อสุขภาพ จังหวัดนครราชสีมา มีขีดความสามารถในการแข่งขันเพิ่มขึ้นในภาพรวมอยู่ในระดับมากและหากพิจารณาในรายละเอียดพบว่าด้านการเพิ่มความรู้ในการดำเนินธุรกิจเพิ่มขีดความสามารถในการแข่งขันสูงสุด รองลงมาคือ ด้านการสร้างนวัตกรรม และด้านการเพิ่มประสิทธิภาพการดำเนินงาน ตามลำดับ Capability Development of SMEs through Cluster-based Approach: Healthy Food Industrial Cluster in Nakhon Ratchasima Province This research aims to study the competitiveness of entrepreneurs of healthy food industrial cluster in Nakhon Ratchasima, Thailand, developed by SMEs entrepreneurs using the cluster development approach, which is under a procedure of research and development. The research results found that the entrepreneurs of healthy food industrial cluster has the ability to increase the overview competition in many levels, moreover it has been considered intoits details which reveals the aspects in surging knowledge of business operation and enhancing the maximum competitive innovation and productivity of operations, respectively.